PENGARUH PEMANFAATAN ELEKTRONIK-MONITORING PELAKSANAAN ANGGARAN, KOMITMEN ORGANISASI DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA PELAKSANAAN ANGGARAN PADA KANTOR KEMENTERIAN AGAMA DALAM WILAYAH PROVINSI ACEH - Safrizal, Darwanis, Heru Fahlevi (Jurnal Akuntansi, 2017)
Abstract: The purpose of this research is to examine the effect of utilization electronic-monitoring of budget execution, organizational commitment, and human resources competencies, either simultaneously or partialy toward the performance implementation of the budget on ministry of religious offices in the province of Aceh. This is a hypothesis testing research which is based on the data that collected by questionnaires and analyzed using multiple linear regression analysis. The population in this study are all religious ministry offices in the province of Aceh (23 work unit), with the respondents amounted to 69 apparatus of responsible for implementing the budget in each work unit. The results showed that the electronic-monitoring of budget execution, organizational commitment, and human resources competencies affects the performance implementation of the budget either simultaneously or partially.Keywords:   Electronic-monitoring of budget execution, organizational commitment, human resources competencies, and performance implementation of the budgetAbstrak: Penelitian ini bertujuan untuk menguji pengaruh pemanfaatan-elektronik monitoring pelaksanaan anggaran, komitmen organisasi, dan kompetensi sumber daya manusia terhadap kinerja pelaksanaan anggaran pada Kantor Kementerian Agama dalam wilayah Provinsi Aceh. Penelitian ini merupakan penelitian pengujian hipotesis dengan sumber data yang dikumpulkan dengan kuesioner dan dianalisis dengan menggunakan analisis regresi linier berganda. Populasi dalam penelitian ini adalah seluruh Kantor Kementerian Agama dalam wilayah Provinsi Aceh (23 satuan kerja), dengan responden berjumlah 69 orang pelaksana dan penanggungjawab anggaran pada masing-masing satuan kerja. Hasil penelitian menunjukkan bahwa pemanfaatan-elektronik monitoring pelaksanaan anggaran, komitmen organisasi, dan kompetensi sumber daya manusia berpengaruh terhadap kinerja pelaksanaan anggaran baik secara simultan maupun parsial.Kata kunci:  Elektronik-monitoring pelaksanaan anggaran, komitmen organisasi,  kompetensi sumber daya manusia, dan kinerja pelaksanaan anggaran